2017
DOI: 10.26480/msm.01.2017.19.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Season on Occurrence of Caprine Mastitis in Beetal in Faisalabad Premises

Abstract: Mastitis in goats, analogous to dairy cattle, is one of the most significant diseases of economic importance, worldwide. For the proposed study 25 Beetal Faisalabadi goat farms comprising 10-20 goats in radius of 25 km was included. Sampling was done during two kidding season first in September-October and second in FebruaryMarch. The epidemiological data, including goat breed, age, parity, stage of lactation, amount of milk, length of lactation period, and farming system were recorded. These selected herds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
6
14
0
1
Order By: Relevance
“…Mastitis prevalence in small ruminants has been reported by Fox and Gay, 1993;Bergonier et al, 2003;Contreras et al 2003;Contreras et al 2007;Ali et al 2010;Megersa et al, 2010;Islam et al, 2011;Islam et al, 2102;Bourabah et al, 2013 andRashid et al, 2017. The current study's findings agree with outcomes of study reported by Megersa et al (2010).…”
Section: Goat Strains Related Distribution Of Samplessupporting
confidence: 90%
See 4 more Smart Citations
“…Mastitis prevalence in small ruminants has been reported by Fox and Gay, 1993;Bergonier et al, 2003;Contreras et al 2003;Contreras et al 2007;Ali et al 2010;Megersa et al, 2010;Islam et al, 2011;Islam et al, 2102;Bourabah et al, 2013 andRashid et al, 2017. The current study's findings agree with outcomes of study reported by Megersa et al (2010).…”
Section: Goat Strains Related Distribution Of Samplessupporting
confidence: 90%
“…The flock size has significant effect (P<0.05), as the flock size of 21-40 goats has 46.5% followed by 1-20 goat head 28.8% and more than 40 head 23.7%. This finding is very close to the results about flock size of Megersa et al 2010 andRashid et al, 2017. Body condition score has shown that there was highly significant (P<0.001) difference presenting poor and good having 42.4% and 15.2%, respectively while excellent to be 0.1%. The findings were again in agreement with Megersa et al 2010 andRashid et al, 2017.…”
Section: Goat Strains Related Distribution Of Samplessupporting
confidence: 89%
See 3 more Smart Citations